Improved Detection of Emerging Drug-Resistant Mutant Cytomegalovirus Subpopulations by Deep Sequencing - Chou, Sunwen (American Society for Microbiology, 2014)
In immunosuppressed hosts, the development of multidrug resistance complicates the treatment of cytomegalovirus (CMV) infection. Improved genotypic detection of impending drug resistance may follow from recent technical advances. A severely T-cell-depleted patient with chronic lymphocytic leukemia developed CMV pneumonia and high plasma viral loads that were poorly responsive to antiviral therapy. Serial plasma specimens were analyzed for mutant viral populations by conventional and high-throughput deep-sequencing methods. Uncharacterized mutations were phenotyped for drug resistance using recombinant viruses. Conventional genotyping detected viruses with the UL97 kinase substitution C607Y after ganciclovir treatment, a transient subpopulation of UL54 polymerase L773V mutants first detected 8 weeks after foscarnet was started, and a subpopulation of a mutant with deletion of UL54 codons 981 and 982 2 months after the addition of cidofovir. Deep sequencing of the same serial specimens revealed the same UL54 mutants sooner, along with a more complex evolution of known and newly recognized mutant subpopulations missed by conventional sequencing. The UL54 exonuclease substitutions D413N, K513R, and C539G were newly shown to confer ganciclovir-cidofovir resistance, while L773V was shown to confer foscarnet resistance and add to the ganciclovir resistance conferred by UL97 C607Y. Increased sequencing depth provided a more timely and detailed diagnosis of mutant viral subpopulations that evolved with changing anti-CMV therapy.